EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN KOOPERTIF TIPE STAD KELAS VII SMP NEGERI 1 SUNGAI RAYA - Meida, Sri; Mashudi, Mashudi; Buwono, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research is to determine the effectiveness of applying cooperative learning model of Student Team Achievement Division type in the subject of Social Science at Class VII of SMP Negeri 1 Sungai Raya. The method of this research is experimental research with Quasi Experimental research form and Nonequivalent Control Group Design. The subjects of this research were students of class VII C and VII E Junior High School 1 Sungai Raya which consists of 62 students. The technique of data collection used in this study is measurement technique. The tools of data collection used in this study are observation sheet, learning result test, observation sheet and note sheet. The results showed that the experimental class learning outcomes were higher than the control class, because the improvement of the students' experimental learning result was 31.93 while the control class only increased by 21.94. Based on the T-test result of experimental class and control class, it was obtained that t-arithmetic > t-table (3,796> 2.00). It showed that Ho is rejected and Ha is accepted. Thus, it can be concluded that the Model Students Teams Achievement Divisions (STAD) is effective to be applied in Social Science subject at class VII in SMPN 1 Sungai Raya.Â Keywords:Â  Cooperative Learning Model Model type STAD, Learning Outcomes.